2017
DOI: 10.1016/j.combustflame.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive-thermal effect on local chemical structures in premixed hydrogen–air flames

Abstract: The diffusive-thermal effect plays an important role in the intrinsic instability of premixed flames. A two-dimensional direct numerical simulation of the propagation of premixed hydrogen-air flames was performed using a detailed chemical kinetics model. The cellular behavior of a lean hydrogen-air flame was analyzed on the basis of its chemical structure.The primary consequence of the diffusive-thermal effect was found to be a change in the buildup process of reactive intermediates by the chain reaction mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In particular, for Le = 1 and ratios of the plate separation h to the thermal flame thickness δ T of the order a ≡ h/δ T = S L h/D Tu ≈ 15, where a can be interpreted as a Peclet number, the authors reported an overall flame speed S T 1 of about 1.4 times that of the adiabatic planar velocity S L . Excluding ST by neglecting the viscous drag due to Poiseuille flow, S T /S L decreased to about 1.25, in agreement with values previously calculated for purely 2D simulations that included DL but not ST effects [33,34,35,36,37]. Experimental studies have investigated and identified the contributions of some of these intrinsic instability mechanisms in Hele-Shaw cells [39,38,40], making use of different mixtures, direction of propagation and distance between the plates.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…In particular, for Le = 1 and ratios of the plate separation h to the thermal flame thickness δ T of the order a ≡ h/δ T = S L h/D Tu ≈ 15, where a can be interpreted as a Peclet number, the authors reported an overall flame speed S T 1 of about 1.4 times that of the adiabatic planar velocity S L . Excluding ST by neglecting the viscous drag due to Poiseuille flow, S T /S L decreased to about 1.25, in agreement with values previously calculated for purely 2D simulations that included DL but not ST effects [33,34,35,36,37]. Experimental studies have investigated and identified the contributions of some of these intrinsic instability mechanisms in Hele-Shaw cells [39,38,40], making use of different mixtures, direction of propagation and distance between the plates.…”
Section: Introductionsupporting
confidence: 80%
“…Calculations neglecting the transverse confinement [33,34,35,36,37], that is, for purely 2D freely propagating flames without confinement, predict a propagation speed of S T /S L ≈ 1.2. This speed increases when the transverse confinement is included in Hele-Shaw cells, through expansion-induced straining effects, to S T /S L ≈ 1.4 if a = 15 [32] and to S T /S L ≈ 2.2 in the limit of large viscosity effects (a → 0) proposed in the present work.…”
Section: Influence Of the Viscosity Contrastmentioning
confidence: 99%